Foreign Trade of Biomass for Energy Purposes in Poland in the Years 2008–2014 - Barbara Gradziuk; Piotr Gradziuk (Barometr Regionalny, 2015)
The obligation of renewable energy production and the opportunities for additional large revenue from green certificates has led to an increased interest in biomass derived from imports. During the period under study, imports of biomass to Poland increased nearly eight times: from 423 thousand tons to 3 591 thousand tons. Agro biomass imports showed higher dynamics (1160%), including in particular sunflower husks and sunflower and palm oil cake. During the same period, imports of forest biomass increased by 478%, of mainly firewood and wood chips. By 2007, the vast majority of imported biomass had come from the current European Union countries (nearly 50%, the highest amounts from Lithuania, Latvia, Slovakia and Germany), and the structure of imports was divided roughly evenly into agro and forestry sourced biomass. The introduction of mandatory restrictions on the use of forest biomass resulted in a significant increase in non-forest biomass share in the total imports of biomass, which have also significantly increased from year to year. In the last three years, agro biomass imports from the EU and Ukraine have accounted for almost 65% of total imports of biomass for energy purposes. A dramatic increase has also been observed in the imports of exotic biomass, although in relatively small absolute values: from 0 in 2009 to about 65 thousand tonnes in 2010 and 2011, and to more than 600 thousand tonnes in 2014.